Hormonal prevention of breast cancer: Mimicking the protective effect of pregnancy - Guzman, Raphael C. (The National Academy of Sciences, 1999)
Full term pregnancy early in life is the most effective natural protection against breast cancer in women. Rats treated with chemical carcinogen are similarly protected by a previous pregnancy from mammary carcinogenesis. Proliferation and differentiation of the mammary gland does not explain this phenomenon, as shown by the relative ineffectiveness of perphenazine, a potent mitogenic and differentiating agent. Here, we show that short term treatment of nulliparous rats with pregnancy levels of estradiol 17β and progesterone has high efficacy in protecting them from chemical carcinogen induced mammary cancers. Because the mammary gland is exposed to the highest physiological concentrations of estradiol and progesterone during full term pregnancy, it is these elevated levels of hormones that likely induce protection from mammary cancer. Thus, it appears possible to mimic the protective effects of pregnancy against breast cancer in nulliparous rats by short term specific hormonal intervention.